Spatial Memory Bias in Children Tourists. Issue 1 (2nd January 2020) - Huang, Xiaoting; Zhang, Linlin; Ihnatoliova, Lucie
ABSTRACT: What do children absorb from tourism activities? Memory can provide answers to this question – but children's memories do not necessarily tell the truth. Their recollections could be blurred by time, interference, or imagination. Taking Ocean Park Hong Kong as a case study, this research was carried out to explore children tourists' spatial memory bias by matching activity paths based on GPS recordings and recall diaries via biological sequence alignment. False memories and forgetting are the two types of memory bias of interest in this paper. Findings show that false memories, compared to forgetting, are often generated from later parts of the tourism experience. The spatial distribution of tourism memory bias is influenced by the entrance effect, aggregation effect, and competition effect. These results provide new insight into research on children education and tourist memory.